Teacher Competencies and Parental Cooperation - Westergard, Elsa (International Journal about Parents in Education, 2023)
The aim of this paper is to begin to shed light on the competencies teachers need when cooperating with parents. Toward this end, we conducted a small-scale study, interviewing teachers and parents about their perceptions of teachers’ competence regarding cooperation with parents. Sixteen pairs of cooperating parents and teachers at a primary school, agreed to participate in separate interviews. The interviews were based on semi-structured interview guides. The NVIVO program was used to assist data analyses. Building on research regarding parental disillusionment with school and the small-scale study, the paper reveals a need for competence-building activities at various levels in schools. First, the principal plays an important role in this process by building collective competence at the school level, such as routines and school standards for cooperation with parents. Second, colleagues’ collective competence in cooperating with parents is important. Finally, each teacher’s individual competence in cooperating with parents is an important factor regarding parental cooperation. We identify three separate individual competencies.